Thermodynamics of CO2 Adsorption on Polyethyleneimine Mesoporous Silica and Activated Carbon - Al-Marri, J.; Al-Saad, K.; Saad, M. A.; Cortes, D. J.; Khader, M. M. (My University, 2017)
A thermodynamic study of the enthalpies of adsorption of CO2 was conducted on polyethyleneimine 10k/ mesoporous silica (PEI-10k/MPS) and activated carbon (AC). These materials were chosen because of their high CO2 sorption capacities at about 85°C for PEI and about 20°C for the AC, therefore can capture CO2 with high efficiency in a wide temperature range. The absolute quantity of adsorbed CO2 as a function of equilibrium pressure at various temperatures was determined experimentally and fitted to isotherms of generalized Langmuir and Toth equations for PEI and AC, respectively. The adsorption of CO2 on PEI was favored with temperature revealing the endothermic nature of the process. On the other hand, CO2 adsorption on the AC was exothermic. The isosteric enthalpy of adsorption on PEI was about constant with CO2 loading at a value of 93 kJ.mol-1, confirming its chemical nature and corroboration with the Langmuir model. The corresponding isosteric enthalpy of the AC was in the range of ~-25 kJ.mol-1 and was continuously decreasing with CO2 loading; confirming the physisorption nature of the process and also that CO2/ CO2 interactions within the adsorption layer was significant.
Keywords: Isosteric enthalpy of adsorption; Polyethyleneimine 10k/ mesoporous silica; Activated carbon